Plantar fascia stiffness accounts for individual variance in its strain during hopping at different frequencies in females - Hobo, A. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The plantar fascia (PF) behaves like a spring during bouncing gait, whereas its strain is a potential risk factor for plantar fasciitis. PF strain in bouncing gait is determined theoretically by complex foot dynamics, involving numerous active and passive foot structures, but the determinants of its individual variability remain unclear. Here we show the high relevance of PF stiffness to its strain in hopping by 11 females. PF stiffness, assessed as shear wave velocity, correlates with peak PF strain in hopping at different frequencies (1.8, 2.6, 3.4 Hz). The variance accounted for increases with increasing hopping frequency (from 49 to 68%), indicating greater dependence of PF strain on its stiffness at higher frequencies. We suggest that practitioners improve PF mechanical properties by applying repetitive loads via bouncing gait to modulate PF strain and prevent foot injuries, including plantar fasciitis.